The Influence of Customer Experience and E-Service Quality on LinkAja Syariah Users' E-Loyalty with E-Customer Satisfaction as an Intervening Variable - Verdiana, Maishifa Avis; Yunadi, Ahmad; Salam, Abdul; Sujono, Rusny Istiqomah (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2025)
This research aims to analyze the influence of Customer Experience and E-Service Quality on E-Loyalty of LinkAja Syariah users in Indonesia, with E-Customer Satisfaction as an intervening variabel. The sample used consisted of 100 LinkAja Syariah user respondents who had actively used the application in the last six months and were over 17 years old, who were selected using a nonprobability sampling technique, namely purposive sampling. The collected data was then analyzed using the Partial Least Squares method with the SmartPLS 4.1.0.6 Software application. The research results show that Customer Experience does not have a significant effect on E-Loyalty, but has a positive and significant effect on E-Customer Satisfaction. On the other hand, E-Service Quality is proven to have a positive and significant influence on E-Loyalty and E-Customer Satisfaction. Apart from that, E-Customer Satisfaction has also been proven to have a positive and significant effect on E-Loyalty, and acts as an intervening variabel that mediates the influence of Customer Experience and E-Service Quality on E-Loyalty.